Entrepreneurial self-efficacy and competencies: Reinterpreting entrepreneurial embedded resources - Ahmad Firdause, Md Fadzil; Mukhtar, D.; Sofian, M.F. (2021)
In a new venture development process, entrepreneurs need to have a high degree of self-confidence and competence to perform unique entrepreneurial tasks. These elements are known as built-in entrepreneurial tools. At the early stage of the new entrepreneurship process, it is important to consider these two factors, since they can influence the thought, behaviour and actions of entrepreneurs. The main purpose of this paper is to enhance our understanding of embedded entrepreneurial capital. We analysed and clarified the framework for evaluating entrepreneurial autonomy and skills. We conducted interview with business incubator tenants to compare the growth of entrepreneurial performance and skills. This study empirically demonstrates that the capacity of entrepreneurs to execute business tasks is reflected in their prior experience in executing tasks successfully. Behavioral findings have been a central factor in assessing actual entrepreneurs’ competences in the area of self-confidence. This emphasises the need to move from the emphasis to a relatively important entrepreneurial training programme which takes into account the role of entrepreneurs within the business cycle.